'To Be a Scientist Sometimes You Have to Break Down Stuff about Animals': Examining the Normative Scientific Practices of a Summer Herpetological Program for Children. Issue 3 (2nd July 2016) - Scott, Catherine Marie
Abstract : When studying informal science programs, researchers often overlook the opportunities enabled and constrained in each program and the practices reinforced for participants. In this case study, I examined the normative scientific practices reinforced in one-week-long Herpetology (the study of reptiles and amphibians) program for elementary students. In the program, participants identified four practices that they felt were important to herpetology and felt that the practices in which they engaged reflected those of herpetologists in the field. The practices identified by participants (e.g. use of tools, use of scientific vocabulary) aligned with those identified by herpetologists working with the participants in the program. The findings illustrate that program structure plays a significant role in establishing normative scientific practices. This study (1) encourages researchers to question the ways in which normative practices are developed for participants and (2) suggests that practitioners must not only consider the learning outcomes of informal summer programs, but also the opportunities enabled through participation for elementary children.